The Influence of Demographic Factors and Work Environment on Job Satisfaction Among Police Personnel: An Empirical Study - Kumar, T. K. Vinod (International criminal justice review, 2021)
Job satisfaction among employees is important for police organizations. Low job satisfaction may result in poor organizational commitment, unsatisfactory job performance, and absenteeism. Job satisfaction is impacted by demographic factors and characteristics of the work environment. Analyzing survey data of 6,041 police officers, the study finds that while demographic factors and job characteristics impact job satisfaction, organizational characteristics have the greatest influence. The study illuminates the similarities and differences in organizational dynamics impacting job satisfaction in police organizations in India and other countries and underlines the relevance of the theory across countries and cultures.